Analisis Risiko Usahatani Kopi Robusta di Desa Munduktemu, Kecamatan Pupuan, Kabupaten Tabanan - GUSTI AYU PUTU WIDHI ASTUTI; I WAYAN WIDYANTARA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Risk Analysis of Robusta Coffee Farming in Munduktemu Village, Pupuan Sub-District of Tabanan Regency. Coffee commodity is a species of small tree plantations belonging to the family of Rubiaceae and the genus of Coffea. Munduktemu Village is one of Robusta coffee producing villages in Tabanan. This study aims to determine the level of production and income risks in Robusta coffee farming if analyzed based on farm risk analysis. Based on the results of farm risk analysis, the risk of production is quite high as seen from the standard deviation of 753,45 kg / year and the coefficient of variation value of 0,33. Robusta coffee farmers can avoid production risks with a risk threshold of 753,84 kg / year. The risk of income is quite high as seen from the standard deviation value of Rp. 17,42 / year and the coefficient of variation value is 0,33. Robusta coffee farmers can avoid risk with a risk threshold of Rp 17,85 / year. The Robusta coffee farmers in Munduktemu Village are expected to pay attention to fertilizers and seeds, in order to be able to increase productivity. Alternative ways of handling risks that can be done by respondents in producing Robusta coffee is by conducting partnership farming contracts and conducting agricultural counseling or training in plant cultivation techniques of Robusta coffee, with the expectation that the respondents' Robusta coffee production yields in Munduktemu Village will be higher and more stable in the future.